นโยบายต่างประเทศของลาวหลังสงครามเย็น : ศึกษาปัจจัยที่ส่งผลต่อการปรับนโยบายต่างประเทศ - สิทธิสังคม ศรีสะเกษ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This thesis is making a study on Lao foreign policy in the post-cold war era, concentrating on the internal and external factors which influence Lao foreign policy adaptation. Employing descriptive and analytical approach, this thesis relied heavily on academic work, magazines and other official publications written in Lao, Thai and English as well as some information from websites. The analytical theme of this thesis focuses on economic and political history, both at domestic and external levels, and also employs linkage politics theory as the framework studies. The findings of this thesis were: the internal factors, namely the problem of economic development and the need of economic assistance, and the external factors including the demise of the cold war, and conflicts between Vietnam and Cambodia necessitated Laos’ foreign policy adaptation in the post-cold war era.